Programmatic management of rifampicin-resistant tuberculosis with standard regimen in Cameroon: a retrospective cohort study - Jouego, Christelle Géneviève; Gils, Tinne; Piubello, Alberto; Mbassa, Vincent; Kuate, Albert; Ngono, Annie; Belinga, Edwige; Etoundi, Antoine; Tollo, Alphonse; Makondi, Danielle; André, Emmanuel; Masumbe, Palmer; et al. (International journal of infectious diseases, 2022)
To describe treatment outcomes for rifampicin-resistant tuberculosis (Rr-TB) started on standard regimen and the frequency of acquired drug resistance in patients treated using the standard treatment regimen (STR) in Cameroon between 2015-2019. This is a retrospective cohort study. Rr-TB patients were initiated on the STR, including a fluoroquinolone (FQ), a second-line injectable drug (SLI), and companion drugs. In case of resistance to fluoroquinolones (FQr) at baseline, FQ, SLI and ethionamide were replaced by bedaquiline, delamanid, and linezolid in a modified treatment regimen (mTR), FQr-mTR. In case of resistance to SLI (SLIr) at baseline, SLI was replaced by linezolid (LZD), SLIr-mTR. Logistic regression and competing risk regression were used to estimate predictors of early (first eight weeks) mortality and overall mortality, respectively. Of 709 patients started on a standard regimen, treatment success occurred in 84.7% (587/693), 72.7% (8/11) and 100% (10/10) of patients treated with STR, FQr-mTR and SLIr-mTR as final regimens, respectively. Three (0.6%) patients acquired FQr during treatment. Early mortality occurred in 4.1% (29/709) and was associated with being HIV positive, male sex and being underweight. Overall mortality was associated with missing drug-susceptibility testing results at baseline, being HIV positive, age>40 and male sex. Programmatic management of Rr-TB, with additional second-line drug resistance treated with mTR, resulted in excellent treatment outcomes.